Determination of heavy metal content in traditional Chinese medicines and supplements using atomic absorption spectrometry - Helal Uddin, A.B.M.; Saeed, Mohammad; Mohd Nawi, Mohd Asri (2010)
Use of traditional medicine and health supplements as complementary and alternative medicine is getting popular worldwide. The popularity of traditional medicine and health supplements causes high demand of these products. Proper quality control measures should be taken prior to marketing of these types of medicines and supplements to assure the safety of the products. Heavy metal toxicity is very common in traditional medicines. Various health complications caused by heavy metal toxicity from traditional medicines and supplements are often reported. Screening of heavy metal content in traditional medicines and supplements is become regulatory issue in many developed countries. In this study we have analysed different heavy metal in twenty one different chinese herbal medicine and health supplements collected from different sources. In our study we have used atomic absorption spectroscopy (AAS) for the determination of the metals in the samples. Hollow cathode lamp of different wavelength suitable for particular element was used as a radiation source. Acid digestion method was used for the preparation of the sample prior to analysis with AAS. Acid digestion of the sample facilitate to eliminate or destroy the organic matrix and liberate the metals which will be in free form and easily detectable by AAS. The samples were digested using nitric acid and hydrochloric acid digestion method. The range of the investigated elements were 0.23–3.38 μg/g, 0.05–0.58 μg/g, 1.02–8.75 μg/g, 0.08–0.15 μg/g for Pb, Cd, Ni and As respectively. The level of the content of different heavy metal was found to be under legal limits for traditional medicines set by the local authority. Key words: Chinese medicines, supplements, AAS, Acid digestion.